YIIFSWA II OPENDAY - Interview with Daan Luteyn - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Interview with Daan Luteyn at YIIFSWA-II Open Day. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam